PENTINGNYA MENINGKATKAN MINAT BACA SISWA - Ruslan, Ruslan; Wibayanti, Sri Hayu (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The perpose of this reasearch is to inform about the importance of reading activity to increase perceptoin or knowledge. There are factors that support to increase reading interest especially teachers and students. This report is written with research methodology qualitative descriptive.Data obtained by conducting observations first for 10 days, then was continued by interviews the library SDN 16 Pulau Rimau with  mrs.Damayanti.Speakers concerned considered the most know on a would check, about the effort teachers and in overcoming the low reading interest students. The research results show that which causes the low reading interest students , because students always lazy , students consider read dull and a lot of students who less understand the importance of reading books .Efforts teachers are shed light of understanding to students will the importance of reading and make event or a race that make students avid reader.